2016
DOI: 10.1093/neuonc/now035
|View full text |Cite
|
Sign up to set email alerts
|

AVAREG: a phase II, randomized, noncomparative study of fotemustine or bevacizumab for patients with recurrent glioblastoma

Abstract: Single-agent bevacizumab may have a role in patients with recurrent glioblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
40
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 24 publications
8
40
0
Order By: Relevance
“…The incidence of AEs in second and third lines of treatment was generally similar between the treatment groups, although the incidence of SAEs in second‐line treatment was higher with CCNU + BEV than with CCNU + placebo (18% vs. 7%). The higher rate of thrombocytopenia observed in the CCNU + BEV group than in the CCNU + placebo group is in line with data from the BELOB and AVAREG studies . The high rates of study treatment discontinuation in second and third lines of treatment observed in this study reflect the hastened clinical deterioration upon progression and the difficulty in managing these patients in clinical practice.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The incidence of AEs in second and third lines of treatment was generally similar between the treatment groups, although the incidence of SAEs in second‐line treatment was higher with CCNU + BEV than with CCNU + placebo (18% vs. 7%). The higher rate of thrombocytopenia observed in the CCNU + BEV group than in the CCNU + placebo group is in line with data from the BELOB and AVAREG studies . The high rates of study treatment discontinuation in second and third lines of treatment observed in this study reflect the hastened clinical deterioration upon progression and the difficulty in managing these patients in clinical practice.…”
Section: Discussionsupporting
confidence: 85%
“…Despite first‐line treatment with surgical resection followed by radiotherapy (RT) plus concomitant and adjuvant temozolomide (TMZ) , the prognosis remains poor, with 1‐ and 5‐year glioblastoma survival rates of 39.3% and 5.5%, respectively . In the recurrent setting, chemotherapy remains the main treatment option ; nitrosourea‐based regimens, such as lomustine (CCNU), are the preferred choice . The efficacy of chemotherapeutic agents is limited, and there remains a high unmet medical need to establish effective glioblastoma treatments; anti‐VEGF agents, such as bevacizumab (BEV), have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Response rate was 42.6% and 14.3%, in BEV and FTM arms. Median survival was 7.4 (95%CI 6.0-8.9) and 8.6 (95%CI 6.6-10.8) months, respectively, similarly to the entire population of the study [ 3 ]. After progression, 59.6% and 67.9% of patients in the BEV and FTM arm, respectively, received a third line treatment.…”
Section: Resultsmentioning
confidence: 94%
“…In the multicentric noncomparative, randomized phase II AVAREG trial (EudraCT: 2011-001363-46) [ 3 ], that evaluated the role of bevacizumab (BEV) or fotemustine (FTM) in recurrent GBM, we obtained similar survival with the two compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies indicated that it was associated with better outcome in methylated patients receiving TMZ-containing therapy ( 18 , 19 ). But some studies also showed that it conferred survival benefit in methylated patients receiving TMZ-free therapy ( 21 , 22 ). So it is necessary to review whether the survival benefit from MGMT methylation is therapy dependent or independent, which will define MGMT promoter methylation as a predictive or prognostic biomarker.…”
Section: Introductionmentioning
confidence: 99%